Children with type 1 Diabetes Mellitus: access to special immunobiological and child care - Paula Carolina Bejo Wolkers; Marina Sayuri Yakuwa; Letícia Pancieri; Clesnan Mendes-Rodrigues; Maria Cândida de Carvalho Furtado; Débora Falleiros de Mello (SciELO, 2017)
Abstract OBJECTIVES Identifying the use of child care situations, the vaccination situation and the reasons for non-vaccination, and characterizing whether mothers/guardians demonstrate notions about the right to special vaccines for children with type 1 Diabetes Mellitus. METHOD A descriptive, cross-sectional study with analysis of quantitative data based on interviews with mothers/guardians, particularly regarding access to childcare and vaccination against influenza and pneumococcal 23-valent (PPSV). RESULTS 47 mothers/guardians participated in the study. The participants reported using more specialized services to follow child health, and only a few used the child care of the basic health care regularly. There were incomplete vaccination schedules, delayed annual follow-ups, missing vaccination cards at the consultations, misinformation about the special character of the vaccination, as well as emphasis on the need of presenting a specific form to obtain the vaccination, resulting in discontinuation of health actions and missed opportunities for vaccination. CONCLUSION Fragilities in child care and immunization actions require an increase of primary health care and of the care network, based on knowledge and the right to health in order to expand the evidence-based practice, access and comprehensiveness.